Expressions of Feeling And Gender Differences on Instagram Comments - Pratiwi Susilo (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
This paper discusses gender issue seen from its relation with language differences. The objectives of this paper are examining the relation of gender and language. Moreover, it also differenciates language to gender through Instagram comments. To colect the data, I used an observation method with a note-taking technique. In analaysing the data, I used distributional method for grouping each category of feeling. The result of the study shows that there is a dependence for each gender to depict a different rensponds on using language to express their feeling into words. This finding indicates that different gender will show different rensponse on expressing feeling into words. Keywords: gender differences, expressions of feeling, language, anger, comments.